PENGEMBANGAN MODEL PENDIDIKAN KARAKTER TERINTEGRASI DALAM PEMBELAJARAN BIDANG STUDI DI SEKOLAH DASAR - Darmiyati Zuchdi (LPMPP Universitas Negeri Yogyakarta, 2010)
Abstract: The Development of a Character Education Model Integrated intoSubject Matters in Elementary School. This article is based on the results of thefirst year study of a three-year study aiming to develop a character educationmodel using a comprehensive approach integrated into the learning of theIndonesian language, science, and social studies in elementary school, togetherwith the development of a school culture. The research subjects comprised fourelementary schools in the Province of Yogyakarta, Indonesia. The results of thisstudy revealed that an effective model of character education is one implementinga comprehensive approach integrated into subject matters, using multimethods i.e.inculcation, modeling, value facilitation, and soflt skills development, accompaniedby the development of a positive school culture; the school principal and staffmembers, teachers, and parents should be involved in the practice of charactereducation; and the activities should be conducted in class, out of class, and athome.Keywords: character education, comprehensive approach, integrated learning, school culture